DAHBOARD EKSEKUTIF SEBAGAI MEDIA KOORDINASI DAN MONITORING KEGIATAN UNTUK PENINGKAT KINERJA APARATUR PEMERINTAH - Maulana, Mohammad Reza; Syaifudin, Anas; Budijanto, Hari Agung; Susanto, Eko Budi (BAPPEDA Kota Pekalongan, 2020)
Pekalongan City Government continues to strive to improve good governance in maximizing the use of Information Technology, this is evidenced by the participation of the Pekalongan City Government in the Movement Towards 100 Smart City programs. One effort that can be made to optimize the use of information technology is the executive dashboard for monitoring RT / RW activities. In 2019, Pekalongan City has 340 RW and 1660 RT. The existence of this executive dashboard application can optimize the role of RT and RW and all information at the lower level can be obtained immediately, such as information on population data, submission of grants and assistance, and others. The information in the monitoring dashboard is the realtime data that currently exists. This research will make a dashboard monitoring RT / RW activities with a prototype model approach. The prototype model and Joint Application Development (JAD) are the most widely used models in creating executive dashboards. The research steps started from data collection, data analysis, application design, application development and testing. From the data collected, a functional and non-functional requirements analysis process was carried out. After that the application design process is carried out and conti nued with the design implementation in the application development process. Then from the results of the Alpha Test and Beta Test, the application can work according to functional and non-functional needs. In the future, this application prototype can be developed in conjunction with the One Data application in Dinas Komunikasi dan Informatikan (Diskominfo) Pekalongan City. Keywords: Executive dashboard, smart city, prototype.